Experimental Study on Mechanical Properties and Stability of Marine Dredged Mud with Improvement by Waste Steel Slag - Qiaoling Ji; Yingjian Wang; Xiuru Jia; Yu Cheng (Buildings)
As marine-dredged mud and waste steel slag in coastal port cities continue to soar, the traditional treatment method of land stockpiling has caused ecological problems. Thus, it is necessary to find a large-scale resource-comprehensive utilization method for dredged mud and waste steel slag. This study uses waste steel slag and composite solidifying agents (cement, lime, fly ash) to physically and chemically improve marine-dredged mud. The physical improvement effect of the particle size and dosage of waste steel slag was studied by the shear strength test under the effect of freeze–thaw cycle. Then, based on the Box–Behnken design of the response surface method, the interaction effects of the solidifying agent components on the unconfined compressive strength were studied. Then, the water stability under dry–wet cycles and a microscopic mechanism were analyzed by XRD and SEM tests. The results show that the waste steel slag with a dosage of 30% and a particle size of 1.18~2.36 mm has the best improvement. The interaction between cement and lime and lime and fly ash has a significant effect on the linear effect and surface effect of 7d unconfined compressive strength, and the strength increases first and then decreases with the increase in its dosage. For the 14d unconfined compressive strength, only the interaction between cement and lime is still significant. The unconfined compressive strength prediction model is established to optimize the mix ratio of the composite solidifying agent. In the water stability, the water stability coefficients of the 7d and 14d tests are 0.68 and 0.95, respectively, and the volume and mass loss rates are all below 1.5%, showing a good performance in dry–wet resistance and durability. Microscopic mechanism analysis shows that waste steel slag provides an ‘anchoring surface’ as a skeleton, which improves the pore structure of dredged mud, and the hydration products generated by the solidifying agent play a role in filling and cementation. The results of the study can provide an experimental and technical basis for the resource engineering of marine-dredged mud and waste steel slag, helping the construction of green low-carbon and resource-saving ports.